A non-antibiotic antimicrobial drug, a biological bacteriostatic agent, is useful for treating aerobic vaginitis, bacterial vaginosis, and vulvovaginal candidiasis - Zeng, Zhen; Li, Pei; Lu, Jiayi; Li, Xiaoqi; Li, Meng; Wu, Yifan; Zheng, Minzi; Cao, Yang; Liao, Qinping; Ge, Zhaojia; Zhang, Lei (Frontiers in Microbiology, 2024)
Background Vaginitis is a common infection in women, with approximately 75% of women experiencing at least one episode during their lifetime. Although antimicrobial agents are widely used to treat vaginitis, recurrent vaginitis occurs in some patients. Resistance to these agents is the major cause of recurrent vaginitis. Therefore, there is an urgent need to develop novel drugs. Methods We investigated the efficacy of a new biological bacteriostatic agent (BBA), composed of lysozyme, phytoalexin, chitosan oligosaccharide, sinensetin, 18β/20α-glycyrrhizin, and betaine, against vaginitis using in vitro and in vivo studies. We evaluated the antibacterial effects of BBA against 13 microbial strains commonly present in aerobic vaginitis, bacterial vaginosis, vulvovaginal candidiasis, and healthy vaginas. Second, we assessed the safety of various doses of BBA administered orally for 4 weeks in female mice. Furthermore, we examined the in vivo anti-proliferative and anti-inflammatory effects of BBA in Candida-albicans-, Candida-glabrata-, and Gardnerella-induced vaginitis models. Finally, we evaluated the anti-vaginitis effect of a BBA gel prepared with 0.5% (w/v) ammonium acryloyldimethyltaurate/Vp copolymer. Results BBA effectively suppressed the growth of the main causative pathogens of vaginitis in vitro. BBA, either undiluted or diluted two-fold, inhibited all microorganisms cultured for 8 h. No obvious organ damage was detected when BBA was administered to mice. Both BBA alone and 70% BBA in a gel formulation effectively inhibited the proliferation of C. albicans, C. glabrata, and Gardnerella in vaginal lavage samples and alleviated tissue inflammation in mice with vaginitis. The 70% BBA gel performed better than BBA alone at treating vaginitis in mice infected with Gardnerella vaginalis. Conclusions BBA alone and a 70% BBA gel inhibited the growth of pathogens and effectively alleviated inflammation caused by C. albicans, C. glabrata, and G. vaginalis.